Leibniz algebras with absolute maximal Lie subalgebras - Biyogmam, G.R.; Tcheka, C. (Algebra and Discrete Mathematics, 2020)
A Lie subalgebra of a given Leibniz algebra is said to be an absolute maximal Lie subalgebra if it has codimension one. In this paper, we study some properties of non-Lie Leibniz algebras containing absolute maximal Lie subalgebras. When the dimension and codimension of their Lie-center are greater than two, we refer to these Leibniz algebras as s-Leibniz algebras (strong Leibniz algebras). We provide a classification of nilpotent Leibniz s-algebras of dimension up to five.